Letter (copy) : Basque Children's Trust Limited - Tewson, Vincent
1943-02-01 038-0020-001 Secretary's HVT/SS/325 GC/KN 1st February, 1943. Mr. G. Chester, National Union of Boot & Shoe Operatives, The Grange, Earls Barton, Northampton. Dear Mr. Chester, Basque Children's Trust Ltd. Referring to your letter of the 29th instant in regard to the above matter, I think the best way of conveying information to you on this point would be by us having a chat for a few moments. If you could look in and see me the next time you are in the building I should be glad. Yours sincerely, Assistant Secretary. 292/946/38/20(I)